Inter-Ethnic Co-Existence of the Abagusi-Maasai of Transmara Border From 1850 To 1963. - Maranga, Jackson Ondong’a (Jooust, 2024)
There is a long history of intermittent conflict between the Maasai and the Abagusii at the Trans- Mara frontier in Kenya. However, in modern times, communities rarely fight with one another and often work together to responsibly use their shared natural resources. The two entities appear to be engaged in some type of mutually beneficial restructuring and symbiosis. In most cases, people appear to have tactical means of resolving conflicts amicably. Although this trend seems to be dominant today, research on inter-ethnic relations has largely ignored shifting patterns of coexistence, especially the interface between conflict and coexistence. The purpose of this research is to analyze the evolution of the Maasai and Abagusii's peaceful coexistence in the Trans- Mara boundary from 1850 to 1963. The study's objectives are, to establish the nature of co-existence between the Abagusii and Maasai in the Pre- colonial period, interrogate the impact of the establishment of colonial rule on inter-ethnic co- existence between the Maasai and Abagusii before the outbreak of the Second World War (1895-1939) and establish the transformation process of co-existence between the Maasai and Abagusii during Second World War & Decolonization period (1939-1963). The study used Conflict transformation theory, a multi-dimensional analysis which holds that disagreement is an inevitable byproduct of any attempt to reach a unified opinion and is therefore present in any culture. Since the multi-cultural nature of society generates all sorts of conflicts, a reductionist solution may be elicited by political power and economic competitiveness owing to differential distribution of resources. The theory provided a broader lens through which to examine shifts in the degree to which the two communities were able to co-exist. To get to the bottom of this, the study used a historical research design to collect data and analyse the findings. The study used both probability and non-probability sampling methods to recruit a subset of respondents for in-depth interviews. Subsequent to data collection, thematic analysis was applied to generate and organize information based on the objectives of the study. The study established that the Maasai and Abagusii communities have suffered in a number of ways due to the intermittent conflicts. Property have been destroyed, cattle stolen and the crime rate increased because of ethnic strife. Findings also showed local mechanisms have been adopted for survival and to deal with these situations across the different historical periods.
Keywords: Inter-Ethnic Co-Existence of Kenyan communities.; Transformation process of co-existence between the Maasai and Abagusii, Kenya.